Emotionally intelligent leadership : a guide for students - Levy Shankman, Marcy; Allen, Scott J., 1972-; Allen, Scott J.; Haber-Curran, Paige (2015)
"Explores the connection between emotional intelligence and effective leadership"--
Foreword: It's all about relationships / Susan R. Komives -- Introduction -- Consciousness of self -- Emotional self-perception -- Emotional self-control -- Authenticity -- Healthy self-esteem -- Flexibility -- Optimism -- Initiative -- Achievement -- Consciousness of others -- Displaying empathy -- Inspiring others -- Coaching others -- Capitalizing on difference -- Developing relationships -- Building teams -- Demonstrating citizenship -- Managing conflict -- Facilitating change -- Consciousness of context -- Analyzing the group -- Assessing the environment -- Developing emotionally intelligent leadership -- Appendix: EIL overview.
Includes bibliographical references and index.
Keywords: Educational leadership; Teacher effectiveness; Emotional intelligence; EDUCATION / Students & Student Life; BUSINESS & ECONOMICS / Business Communication / General; BUSINESS & ECONOMICS / Leadership; Educational leadership; Emotional intelligence; Teacher effectiveness; Emotional Intelligence